Desenvolvimento regional do território do estado do Tocantins: implicações e alternativas - Oliveira, Nilton Marques de (2015)
This research analyzed the transition from the old northern Goiás State, Brazil, to the creation of the Tocantins State territory and its regional development context from 1990 to 2010. This study is based on the theoretical support of Raffestin on the concept of territorial development. In the first part, some historical elements of the old northern Goiás about the precarious situation of social and economic indicators are recovered, seeking to capture in time and space the creation of the Tocantins State and its integration into the regional and national economy. The second part addresses the regional development issues with the theoretical basis on Douglass North conceptions and completion of the discussion on regional economy using the authors as Christaller, Myrdal, Perroux and Hirschman. Analysis of observation and perception were used as methodology. The estimate of the Regional Development Index (RDI) and the method of regional analysis were used for the quantitative part, permeated by the side data of Instituto de Pesquisa Econômica Aplicada (Ipea) (Applied Economic Research Institute), Relação Anual de Informações Sociais (RAIS) (Annual List of social Information), Instituto Brasileiro de Geografia e Estatística (IBGE) (Brazilian Institute of Geography and Statistics), and United Nations Development Programme (UNDP). The technique of the Discurso do Sujeito Coletivo (DSC) (Collective Subject Discourse) was used for qualitative part through questionnaires and interviews with key stakeholders. Estimating the Index of Regional Development (IRD), the result allows us to organize the municipalities according to their degree of dynamism. It is concluded in all analyzed periods that there are great social and economic inequalities among the one hundred thirty-nine municipalities of Tocantins State. However, the amount of stragglers economic base of municipalities is coming moderately reducing. It was found that the major employer is linked to state and local government. Nonetheless, the economy of Tocantins territory has increased its share in employment generation in the sectors of trade, services, manufacturing, construction, and agricultural branch of activity. The employment multiplier for the State of Tocantins increased from 4,76 in 2000 to 5,11 in 2010, i.e., the State has increased its capacity to generate employment in the primary sector to the non-basic sector of the economy. It was found also that the Belém-Brasília highway (BR-153) constitutes a regional development corridor. Nevertheless, there are great disparities and inequalities among the municipalities of Tocantins, considering one hundred and seventeen municipalities below the base maintenance polo; nineteen municipalities have base maintenance polo of specialization, and only three municipalities (Palmas, Gurupi, and Araguaína) present diversification base pole, i.e., they have more diversification and diffusion base.